CFD evaluation of a jet in cross flow related to a gas turbine burner - Soroush, Akram (My University, 2012)
In order to increase the performance of the burner in the combustor system, the flame behavior has to be understood by studying the flow in the burner. The goal of this thesis is to present an optimized mesh strategy for simulating a jet in cross flow related to the fuel injection nozzle at the burners used in Siemens gas turbines SGT-700 and SGT-800. The optimization is performed in order to acquire the most accurate results with the least number of cells. The approaches in this thesis may be used to improve the fuel-air mixing prediction of the Siemens Industrial Turbomachinery (SIT) burners. For this purpose the behavior of fluid flow and turbulent mixing in a jet in cross flow is investigated. The simulations are carried out using ANSYS CFX v. 13.0 and Fluent v. 13.0. The standard and realizable k-ε turbulence models are implemented. Since the goal is to find a grid independent solution, Fluent is selected as the main tool due to its grid adaption capability. The accuracy of the predicted flow parameters, namely velocities and concentration field, is evaluated using experimental data which are obtained by Siemens Energy at Mulheim, Germany and Orlando USA, in collaboration with Karlsruhe University, Germany. It is shown that by selecting the suitable region for refinement, proper grid resolution in the jet nozzle and considering reasonable channel wall resolution by adding suitable prism layers, accuracy of the results could be improved without unnecessary cell refinement. Also the results confirm the grid independency for velocity profile.
Keywords: Energi; Fastkroppsmekanik; Strömningsmekanik; Energy; Solid mechanics; Fluid mechanics